PENEGAKAN HUKUM PEMERINTAHAN TENTANG KETERTIBAN SOSIAL (GELANDANGAN DAN PENGEMIS) DI KOTA PEKANBARU TAHUN 2018-2019 - Khasanah, Mila; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Bum and beggars are one of the negative effects of development. Understanding inflammation and beggars according to Pekanbaru City Regulation Number 12 Year 2008 Regarding Social Order as follows: a homeless person is a person who lives in a state that is not in accordance with the norms of decent living in the local community and does not have a permanent residence and work and wanders in place general. While beggars are people who earn money by begging in public in various ways the reason to expect the mercy of others.This study aims to describe the government law enforcement on social order, especially homeless and beggars in the city of Pekanbaru, then also to find out the inhibiting factors of the non-optimal implementation of government law enforcement on social order (homeless and beggars). The location of the study was conducted in Pekanbaru City, first in the office of the Pekanbaru City Civil Service Police Unit (Satpol PP), second in the Pekanbaru City Social Service and Pekanbaru City DPRD Secretariat. Furthermore, data collection techniques were carried out by interview and documentation.The results of this study are the implementation of law enforcement carried out by the Pekanbaru City Government Civil Service Police Unit and Civil Servant Investigators who work together with the Pekanbaru City Social Service, which has not been implemented in accordance with Regional Regulation number 12 of 2008. This is caused by several factors such as legal factors. itself, law enforcement factors, facility or facility factors, community factors, and cultural factors.Keywords : Law enforcement, homelessness and beggars, social order